Technical ICT research for Development? Getting from research to practice - Dearden, Andy; Light, Ann; Kanagwa, Benjamin; Rai, Idris (My University, 2010)
In this paper we argue that, if technical ICT research is going to contribute positively to development, the activities of specialized, highly paid ‘researchers’ must be combined with skilled contributions from many other actors. In particular, there is a critical need to develop the capacity available in development organizations, community based organizations, and in local economies, to innovate and to adapt technologies to support their objectives. This suggests that the methods that we adopt in research and in design should be open to local appropriation and contribute to capacity building, and that education programmes are needed in developing countries to support the broader processes of innovation. We describe the Mobile Innovation & Enterprise partnership, which is working to develop the innovation capacity available in Uganda.
Keywords: ICT4D; design methods; mobileHCI; capacity building